BIOCHEMICAL AND TRANSCRIPTOMIC ANALYSIS OF DISEASE RESISTANCE AND EARLY-MATURITY RELATED GENES IN NMR-191 AND NMR-192 RICE MUTANT LINES : Received: 28th August 2024, Revised: 8th September 2024, 10th September 2024 Accepted: 2nd September 2024 - Yip , Tuck Mun; Hussein , Sobri Bin; Ahmad , Faiz Bin; Hase , Yoshihiro; Wong , Ying Pei; Koh , Rhun Yian; Kiong Ling , Anna Pick (MATTER: International Journal of Science and Technology, 2024)
Rice cultivation in Malaysia faces concerns on blast disease, Magnaporthe oryzae attack, and a long maturation period. Generation of new rice mutant lines that possess improved disease resistance and early maturity characteristics are of great importance. Hence, this study aimed to analyze the biochemical characteristics as well as to validate the presence of disease resistance and early maturity-related genes in rice mutant lines (NMR191 and NMR192). After the parent line Pongsu Seribu 2 (PS2) and mutant lines were grown for 14 days, the biochemical tests (total soluble protein content, chlorophyll and proline content) were conducted. The presence of disease resistance and early maturity genes were also analyzed through transcriptomic profiling. The biochemical analyses showed a significant increase in the total soluble protein, chlorophyll and proline content in NMR191 and NMR192 compared to PS2. The transcriptomic profiling analysis revealed that Os07g0129300, Os12g0270300, and Os03g0235000 were the disease-resistance genes whereas Os03g0195300, Os01g0704100, Os11g0143200, Os06g0569900, and Os06g0568600 were the early maturity genes found in NMR191 and NMR192. This study validates that NMR191 and NMR192 could be better varieties than the parent line due to the presence of their early maturity and disease resistance traits.